Aspetti della connessione nel "Decameron" - Dardano, Maurizio (Verbum – Analecta Neolatina, 2002)
This article attempts a description and an analysis of demonstrative pronouns questo and quello used as phrasal connectors in Boccaccio's Decameron. The emphasis is firmly placed on syntactic and textual phenomena, but at the same time semantic and pragmatic aspects have been considered. Comparison with contemporary and later texts starts up an in-depth study of this so far neglected subject concerning the old Italian syntax.